The Conduct of Operations: Glubb Pasha, the Arab Legion, and the First Arab–Israeli War, 1948–49. (November 2019) - Hughes, Matthew
The recent accession by St Antony's College Oxford of papers from British army officer John Bagot Glubb, commander of Transjordan's Arab Legion, affords a remarkable opportunity to test and reimagine significant debates surrounding the first Arab–Israeli war. Glubb's papers establish two points. First, that military operational necessity best explains the actions of the Arab Legion in 1948 and that this was more important than the political objective by Transjordan and Israel to collude to divide Palestine. Second, the papers offer a new, augmented military history of the war taking into account daunting command and logistical challenges faced by the Legion.